Frailty, Age, and Postdialysis Recovery Time in a Population New to Hemodialysis. Issue 9 (30th September 2021) - Fitzpatrick, Jessica; Sozio, Stephen M.; Jaar, Bernard G.; Estrella, Michelle M.; Segev, Dorry L.; Shafi, Tariq; Monroy-Trujillo, Jose M.; Parekh, Rulan S.; McAdams-DeMarco, Mara A.
Visual Abstract: Abstract : Background: Frailty, a phenotype characterized by decreased physiologic reserve and the inability to recover following confrontation with a stressor like hemodialysis, may help identify which patients on incident hemodialysis will experience longer postdialysis recovery times. Recovery time is associated with downstream outcomes, including quality of life and mortality. We characterized postdialysis recovery times among patients new to hemodialysis and quantified the association between frailty and hemodialysis recovery time. Methods: Among 285 patients on hemodialysis enrolled in the Predictors of Arrhythmic and Cardiovascular Risk in End Stage Renal Disease (PACE) study, frailty was measured using the Fried phenotype. Self-reported recovery time was obtained by telephone interview. We estimated the association of frailty (intermediately frail and frail versus nonfrail) and postdialysis recovery time using adjusted negative binomial regression. Results: Median time between dialysis initiation and study enrollment was 3.4 months (IQR, 2.7–4.9), and that between initiation and recovery time assessment was 11 months (IQR, 9.3–15). Mean age was 55 years, 24% were >65 years, and 73% were Black; 72% of individuals recovered in ≤1 hour, 20% recovered in 1–6 hours, 5% required 6–12 hours to recover, and <5% required >12 hours to recover. Those with intermediate frailty, frailty, and age ≤65 years had 2.56-fold (95% CI, 1.45 to 4.52), 1.72-fold (95% CI, 1.03 to 2.89), and 2.35-fold (95% CI, 1.44 to 3.85) risks, respectively, of longer recovery time independent of demographic characteristics, comorbidity, and dialysis-related factors. Conclusions: In adults new to hemodialysis, frailty was independently associated with prolonged postdialysis recovery. Future studies should assess the effect of frailty-targeted interventions on recovery time to improve clinical outcomes.